Implementasi Pendidikan Karakter pada Sekolah Berbasis Pesantren (Studi Kasus di MA Nurul Jadid Paiton dan MA Bustanul Faizin Besuki) - Hasanah, Faizatul; Munif, Muhammad (Global Education Journal, 2024)
This research aims to reveal character education at MA Nurul Jadid Paiton and MA Bustanul Faizin Besuki. The research method used is a qualitative approach, case study type, with a multisite research design. Data collection techniques through observation, interviews, and documentation. Meanwhile, to analyze the data using the Miles and Huberman method of analysis, namely data reduction, data display and verification. With this method, it is hoped that researchers will obtain accurate data. The results of this research show that (1) In forming the character of MA Nurul Jadid students, Nurul Jadid's Santri Pillars are applied, namely the Santri Trilogy and the Santri's Five Awarenesses. The Santri Trilogy is: Paying Attention to the Obligations of Fardhu 'Ain, Being Self-Aware by Abandoning Major Sins, Being Virtuous towards Allah and Creatures. In forming the character of Madrasah Aliyah Bustanul Faizin students apply Asah, Asih and Asuh (3A) in their daily lives. This makes Madrasah Aliyah Bustanul Faizin students have the character of Asah, Asih and Asuh (3A), so that students become virtuous human beings in their daily lives.